Fiscal Sustainability and Policy Issues in the Eastern Caribbean Currency Union - Pellechio, Anthony J. (International Monetary Fund, 2003)
The fiscal position of the Eastern Caribbean Currency Union (ECCU) has deteriorated significantly in recent years, resulting in sharp increases in public debt. The sustainability of public debt is examined using the public sector budget constraint to derive the maximum public-debt-to-GDP ratio that can be sustained based on a country''s projected steady-state primary balance, interest rate on public debt, and economic growth rate. In this context, government deficits and debt in several ECCU member countries appear unsustainable, posing a risk to the stability of the currency union. A critical issue facing member countries is to implement fiscal policies consistent with sustainable public finances and debt to underpin the currency union